Prevalence of patent foramen ovale in a large series of patients with migraine with aura, migraine without aura and cluster headache, and relationship with clinical phenotype - Dalla Volta, G.; Guindani, M.; Zavarise, P.; Griffini, S.; Pezzini, A.; Padovani, A. (Journal of headache and pain, 2005)
A relationship between migraine and patent foramen ovale (PFO) has been observed in relatively small series of patients so far. Furthermore, the exact mechanism underlying such an association remains unknown. In the present study we determined the prevalence of PFO by contrast-enhanced transcranial Doppler (TCD) in a group of 260 patients with migraine with aura (MA+), 74 patients with migraine without aura (MA-), and 38 patients with cluster headache (CH). One-hundred-sixty-one MA+subjects (61.9%), 12 MA-subjects (16.2%), and 14 CH-subjects (36.8%) were PFO-carriers. The association was independent on the frequency of migraine attacks and complexity of aura. Finally, among the 15 patients who had a history of at least one migraine attack occurring during a Valsalva maneuver only one subject turned out to be PFO-carrier. Our findings confirm previous observations of a link between MA+, CH, and PFO. They also suggest that such an association is independent on migraine clinical phenotype and is probably unrelated to the pathogenic mechanism of paradoxical embolism.